Fee-for-Service Payment - An Evil Practice that Must be Stamped Out? - Naoki Ikegami (Kerman University of Medical Sciences, 2015)
Co-opting physicians to regulate Fee-for-Service (FFS) payment is more feasible and simpler to administer than capitation, Diagnosis-Related Groups (DRGs) and pay-for-performance. The key lies in designing and revising the fee schedule, which not only defines and sets the fee for each item, but also the conditions of billing. Adherence to these regulations must be strictly audited in order to control volume and costs, and to assure quality. The fee schedule requires periodic revisions on an item-by-item basis in order to maintain balance among the providers, to list new drugs, devices and equipment, and to reflect the lower market prices of existing ones. Implementing the fee schedule will facilitate the control of balance billing and extra billing, and the introduction of more sophisticated methods of payment in the future.